2007
DOI: 10.1017/s0022215107001235
|View full text |Cite
|
Sign up to set email alerts
|

Physical and emotional disturbances in children with adenotonsillar hypertrophy

Abstract: Recent studies have confirmed the negative emotional effect of adenotonsillar hypertrophy induced obstructive sleep disordered breathing in children aged six to nine years. The main problems are emotional lability, and anxiety and depressive disturbances. Such emotional problems subside in older children (aged 10 to 13 years).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
0
18
0
3
Order By: Relevance
“…Infection and hypertrophy are components of the immunological reaction of adenotonsillar tissues. However, these reactions can cause chronic diseases, such as adenotonsillar, hyperplasia, and recurrent tonsillitis, which often lead to complications, including nasal obstruction, snoring, auditory tube dysfunction, otitis media, and obstructive sleep apnea . Patients afflicted with these complications frequently decide to undergo tonsillectomy or adenotonsillectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Infection and hypertrophy are components of the immunological reaction of adenotonsillar tissues. However, these reactions can cause chronic diseases, such as adenotonsillar, hyperplasia, and recurrent tonsillitis, which often lead to complications, including nasal obstruction, snoring, auditory tube dysfunction, otitis media, and obstructive sleep apnea . Patients afflicted with these complications frequently decide to undergo tonsillectomy or adenotonsillectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Palatine tonsils and adenoids are prominent secondary lymphoepithelial organs associated with the upper respiratory tract, where inhaled antigens first come in contact with host defense cells [1]. Tonsillar hyperplasia and recurrent tonsillitis are common chronic diseases that often lead to complications that include nasal obstruction, recurrent sinusitis, snoring, auditory tube dysfunction, otitis media, obstructive sleep apnea and changes in facial growth and behavioral development [2]. These complications frequently lead to patients undergoing tonsillectomy, which still is one of the most commonly performed pediatric surgical procedures worldwide [3].…”
Section: Introductionmentioning
confidence: 99%
“…ATH resembles an iceberg, in which the invisible part is more drastic especially for children. Recent studies have confirmed the negative emotional effect of ATH which are emotional lability, and anxiety and depressive disturbances induced obstructive sleep disordered breathing in children [47].…”
Section: Discussionmentioning
confidence: 84%